A Comparative Study of Speech Levels in Kelanjuh Lauq Central Lombok and Kelayu East Lombok - Husnawati Husnawati (Universitas Muhammadiyah Mataram, 2018)
Politeness which is reflected in behavior and speech has different standards in every place as a form of cultural treasures. This is motivated by various things, not only social stratification in society and nobility, but also age, education, familiarity, and speech situation. The community members of Kelanjuh Lauq Central Lombok use Sasak